A kind of iron-nickel-sulfur-based heterojunction catalytic material and its preparation method and application
By constructing a Z-shaped heterojunction structure of FeNi2S4 and Bi2O2CO3, the deficiencies of bismuth-based photocatalytic materials in visible light absorption and charge separation are solved, and efficient organic pollutant degradation and material stability and recyclability are achieved.
Patent Information
- Application Number
- CN202411429431.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The existing bismuth-based photocatalytic materials have shortcomings in visible light absorption and charge separation, resulting in low photocatalytic activity and also have problems with retrievalability and stability in the aqueous phase.
By constructing an iron-nickel-sulfur-based heterojunction catalytic material, FeNi2S4 is combined with Bi2O2CO3 to form a Z-shaped heterojunction structure, which enhances the material's visible light absorption and interface charge separation efficiency, and improves the material's stability and recyclability.
It has achieved an iron-nickel-sulfur-based photocatalytic nanocomposite with stronger interfacial carrier separation ability, light absorption range covering the entire visible spectrum, and higher catalytic activity. It can efficiently degrade organic pollutants and has good stability and reusability. sex.
Smart Images

Figure CN118950034B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalysts, and specifically relates to a novel iron-nickel-sulfur-based heterojunction catalytic material and a preparation method and application thereof. Background Art
[0002] Photocatalytic technology has the advantages of environmental protection and mild reaction conditions, and shows broad application prospects in removing organic pollutants from water. Bismuth-based photocatalytic materials have attracted widespread attention in the field of photocatalysis in recent years due to their strong photocatalytic activity. Among them, bismuth subcarbonate (Bi2O2CO3), as a Sillén-Aurivilius phase compound, has attracted widespread attention due to its significant photocatalytic activity, low cost, non-toxicity and chemical stability. Bi2O2CO3 has a unique layered structure, consisting of [Bi2O2] 2+ Layer and [CO3] 2- The polarization electric field induced between the layers accelerates the transfer and separation of electron-hole pairs. This unique layered structure is composed of [Bi2O2] 2+ and CO3 2- Alternately formed, this can speed up the migration of active species between the two layers. In addition, Bi2O2CO3 has a stable structure, an adjustable band gap, and the potential to undergo visible light-driven reactions. At the same time, a wider band gap means that a higher excitation energy is required, which results in higher redox capabilities for the photogenerated electron-hole pairs from Bi2O2CO3. However, the band gap of Bi2O2CO3 is 3.3-3.5 eV, and only ultraviolet light can activate it. And ultraviolet light accounts for only 5% of the entire solar spectrum, resulting in low photocatalytic activity. In addition, the rapid recombination of photogenerated charge carriers will also inhibit the practical application of Bi2O2CO3. In addition, the rapid recombination of photogenerated charge carriers will also inhibit the practical application of Bi2O2CO3. Therefore, it is necessary to adjust its electronic structure and apply it to the photocatalytic degradation of organic pollutants.
[0003] Constructing a heterojunction is one of the effective strategies to solve these problems. The formation of a heterojunction can not only broaden the light absorption range, but also accelerate the separation of photoinduced charge carriers. People usually use other bismuth-based materials (such as BiOBr, Bi2O3, Bi2WO6) to composite with Bi2O2CO3 to solve the problems of insufficient visible light absorption and insufficient charge separation. However, the visible light absorption of such bismuth-based materials is still limited. For example, the light absorption cutoff edge of BiOBr is about 400 nm, the light absorption cutoff edge of Bi2O3 is about 560 nm, and the light absorption cutoff edge of Bi2WO6 is about 430 nm. This shows that these materials cannot well improve the visible light absorption of composite materials to the full visible spectrum, and even require other doping strategies for further modification. At the same time, the recyclability and stability of the material are still problems faced by such bismuth-based heterojunctions.
[0004] Iron nickel sulfide (FeNi2S4), a typical spinel bimetallic sulfide, has been widely used in electrocatalysis and battery fields due to its advantages such as chemical durability, shape controllability and moderate conductivity. In recent years, researchers have tried to introduce it into the field of photocatalysis and found that it has significant advantages in this field, including low cost, electrical conductivity, photothermal effect and recyclability. However, the current synthetic routes that can be used to prepare nanoscale FeNi2S4 catalysts with controllable phases are still limited. Therefore, designing FeNi2S4 catalysts with well-defined nanostructures through a simple strategy is of great significance for designing efficient heterojunction photocatalysts. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a novel iron-nickel-sulfur-based heterojunction catalytic material, so as to obtain an iron-nickel-sulfur-based heterojunction catalytic material with a simple preparation method, a clear nanostructure, stronger visible light absorption, higher interface charge separation efficiency, better stability, reusability, and the ability to achieve photocatalytic degradation of organic pollutants.
[0006] Another object of the present invention is to provide a novel iron-nickel-sulfur-based heterojunction catalytic material.
[0007] Another object of the present invention is to provide an application of a novel iron-nickel-sulfur-based heterojunction catalytic material.
[0008] The technical solution of the present invention is: (one)
[0010] A method for preparing a novel iron-nickel-sulfur-based heterojunction catalytic material comprises the following steps:
[0011] A. Dissolve Ni(NO3)3·6H2O, Fe(NO3)3·9H2O and urea in deionized water in a certain mass ratio, then add an appropriate amount of ammonium fluoride to the above solution, stir magnetically, wash with deionized water and ethanol by centrifugation for 3-6 times, collect yellow powder, and dry to obtain an iron-nickel material precursor; then mix the iron-nickel material precursor with a thioacetamide sulfur source and dissolve in ethanol, stir the suspension magnetically and heat it continuously at a certain temperature, centrifuge, wash, dry and collect to obtain the material FeNi2S4;
[0012] B. Dissolve a certain amount of FeNi2S4, Bi(NO3)3·5H2O and urea in deionized water, stir and transfer the solution to a polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction. After the reactants are cooled, filter, wash and dry to obtain the heterojunction catalytic material FeNi2S4 / Bi2O2CO3.
[0013] As a further improvement of the present invention, in step A, the mass ratio of Ni(NO3)3·6H2O, Fe(NO3)3·9H2O, urea and ammonium fluoride is 1:0.7-0.9:7-9:0.7-0.9.
[0014] As a further improvement of the present invention, in step A, the mass ratio of the iron-nickel material precursor to thioacetamide is 1:1.2-1.6.
[0015] As a further improvement of the present invention, in step A, the heating temperature is 100-120° C. and the duration is 4-6 hours.
[0016] As a further improvement of the present invention, in step B, the mass ratio of FeNi2S4, Bi(NO3)3·5H2O and urea is 1:2-5:0.5-1.
[0017] As a further improvement of the present invention, in step B, the temperature of the hydrothermal reaction is 180-220° C., and the time of the hydrothermal reaction is 1-3 h.
[0018] Heterojunction composite materials are synthesized through a multi-step combined process, which is costly, time-consuming and labor-intensive. The present invention designs a FeNi2S4 catalyst with a clear nanostructure through a simple method, and combines it with Bi2O2CO3 to construct a heterojunction, which is of great significance for designing efficient heterojunction photocatalysts. (two)
[0020] A novel iron-nickel-sulfur-based heterojunction catalytic material is prepared by the preparation method of the novel iron-nickel-sulfur-based heterojunction catalytic material. (three)
[0022] Application of a new type of iron-nickel-sulfur-based heterojunction catalytic material in visible light photocatalytic degradation of organic pollutants.
[0023] Further, the organic pollutants include bisphenol A.
[0024] The valence band position of Bi2O2CO3 is about 1.8 V, and the conduction band position is about -1.5 V, while the valence band position of FeNi2S4 is about 2.2 eV, and the conduction band position is 0.4 V. Therefore, the matching valence band and conduction band positions between FeNi2S4 and Bi2O2CO3 enable the two to form a heterojunction structure. When excited by visible light, the electrons on the conduction band of FeNi2S4 can be transferred across the heterojunction interface to the surface of Bi2O2CO3, thereby improving the separation efficiency of photogenerated carriers of Bi2O2CO3 under visible light excitation.
[0025] The wide band gap of Bi2O2CO3 means that when the material is excited by light, the photogenerated electron-hole pairs generated have higher redox ability, so that they react with water molecules and dissolved oxygen to generate a variety of active oxidizing substances to efficiently degrade pollutants. The Z-type heterostructure constructed by the present invention allows the photogenerated electrons of FeNi2S4 to be transferred across the heterojunction interface to Bi2O2CO3, reducing the recombination of electron-hole pairs and greatly enhancing the light absorption of Bi2O2CO3 in the visible light region. At the same time, the magnetic composite material solves the problem of the recyclability of powder materials in the water phase and improves the stability of the material.
[0026] The beneficial effects of the present invention are as follows: the present invention composites FeNi2S4 and Bi2O2CO3 by constructing a heterojunction, thereby constructing an iron-nickel-sulfur-based photocatalytic nanocomposite material, FeNi2S4 / Bi2O2CO3, which has stronger interface carrier separation ability, light absorption range covering the entire visible spectrum, and higher catalytic activity. Bi2O2CO3 has no visible light absorption and low charge separation efficiency. The use of traditional bismuth-based materials to composite it cannot achieve effective full visible spectrum absorption, and further modification is still required, resulting in complex synthesis steps. FeNi2S4 avoids such problems, and has better optical absorption than traditional BiOBr, Bi2O3, and Bi2WO6. It can also solve the problem of recyclability and reusability of bismuth-based materials in aqueous phase. By composite FeNi2S4 and Bi2O2CO3, the photogenerated electron-hole pairs of FeNi2S4 / Bi2O2CO3 composite photocatalytic nanomaterials are successfully separated at the heterojunction, avoiding the electron-hole recombination problem in the band gap of a single nanomaterial, and the appropriate energy level position arrangement enables the two to accelerate the migration and separation of photogenerated charges. The construction of the heterojunction more effectively enhances the charge separation and electron transfer at the heterojunction interface, greatly improving the photocatalytic activity. Ultimately, the FeNi2S4 / Bi2O2CO3 photocatalytic system achieves effective pollutant degradation, and has the characteristics of simple synthesis method, good stability and reusability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope image of FeNi2S4 / Bi2O2CO3 prepared in Example 1 of the present invention;
[0028] Figure 2 The ultraviolet diffuse reflectance spectra of FeNi2S4 / Bi2O2CO3, FeNi2S4 and Bi2O2CO3 prepared in Example 1 and Comparative Examples 1 and 2 of the present invention are shown;
[0029] Figure 3 XRD spectra of FeNi2S4 / Bi2O2CO3, FeNi2S4, and Bi2O2CO3 prepared in Example 1 and Comparative Examples 1 and 2 of the present invention;
[0030] Figure 4 This is a performance comparison chart of the photocatalytic degradation of bisphenol A by FeNi2S4 / Bi2O2CO3, FeNi2S4, and Bi2O2CO3 prepared in Example 1 of the present invention and Comparative Examples 1 and 2;
[0031] Figure 5 This is a comparison chart of the reusability experiment of FeNi2S4 / Bi2O2CO3 prepared in Example 1 of the present invention for photocatalytic degradation of bisphenol A. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with specific implementation modes.
[0033] Embodiment 1,
[0034] A method for preparing a novel iron-nickel-sulfur-based heterojunction catalytic material, characterized by comprising the following steps:
[0035] A. 1.04 g Ni(NO3)3·6H2O, 0.73 g Fe(NO3)3·9H2O and 7.57 g urea were dissolved in 50 mL deionized water in sequence, and then 0.74 g ammonium fluoride was added to the above solution. After magnetic stirring at 600 r / min for 30 min, the solution was washed 3-6 times with deionized water and ethanol by centrifugation, and the yellow powder was collected and dried at 80 °C for 12 h to obtain the iron-nickel material precursor; then 0.4 g of the iron-nickel material precursor was mixed with 0.556 g thioacetamide (sulfur source) and dissolved in 70 mL ethanol, and the suspension was magnetically stirred at 600 r / min and heated at 120 °C for 4 h, centrifuged, washed 6 times with ultrapure water and anhydrous ethanol, and dried in an oven at 60 °C for 24 h to obtain black powder FeNi2S4;
[0036] B. Dissolve 1.0 g FeNi2S4, 2.456 g Bi(NO3)3·5H2O and 0.5 g urea in 70 mL deionized water. After mechanical stirring at 600 r / min for 1 h, transfer the solution to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction and heat at 200 °C for 2 h. After the reactants are cooled, filter them, wash them with deionized water and ethanol for 3-6 times, and dry them in an oven at 60 °C for 24 h to obtain the heterojunction catalytic material FeNi2S4 / Bi2O2CO3.
[0037] Figure 1 This is a scanning electron microscope image of FeNi2S4 / Bi2O2CO3 prepared in Example 1. Figure 1 As shown, FeNi2S4 nanoparticles are distributed on Bi2O2CO3 nanosheets, and this in-situ grown close contact provides a channel for rapid photoinduced charge transfer across the heterointerface.
[0038] Comparative Example 1
[0039] Prepare FeNi2S4 only:
[0040] 1.04 g Ni(NO3)3·6H2O, 0.84 g Fe(NO3)3·9H2O and 8.52 g urea were dissolved in 50 mL deionized water in sequence, and then 0.88 g ammonium fluoride was added to the above solution. After magnetic stirring at 600 r / min for 30 min, the solution was centrifuged and washed 3-6 times with deionized water and ethanol, and the yellow powder was collected. After drying at 60 °C for 24 h, the iron-nickel material precursor was obtained; 0.6 g of the iron-nickel material precursor was mixed with 0.667 g thioacetamide (sulfur source) and dissolved in 70 mL ethanol. The suspension was magnetically stirred at 600 r / min and heated at 100 °C for 6 h. After centrifugation, ultrapure water and anhydrous ethanol were washed for 6 times, and dried in an oven at 60 °C for 24 h, the black powder FeNi2S4 was collected.
[0041] Comparative Example 2
[0042] Prepare only Bi2O2CO3:
[0043] 4.912 g Bi(NO3)3·5H2O and 1.0 g urea were dissolved in 90 mL deionized water. After mechanical stirring at 600 r / min for 1 h, the solution was transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction and heated at 220 °C for 1 h. After the reactants were cooled, they were filtered, washed with deionized water and ethanol for 3-6 times, and dried in an oven at 60 °C for 24 h to obtain the product Bi2O2CO3.
[0044] Figure 2 The ultraviolet diffuse reflectance spectra of FeNi2S4 / Bi2O2CO3, FeNi2S4, and Bi2O2CO3 prepared in Example 1 and Comparative Examples 1 and 2 are shown in FIG. Figure 2 As shown in the figure, FeNi2S4 exhibits strong spectral absorption in the entire ultraviolet and visible light regions, and its spectral absorption is significantly enhanced compared to the limited light absorption cutoff edge of traditional bismuth-based materials. The light absorption cutoff edge of single Bi2O2CO3 is about 380 nm, indicating that its absorption of visible light is weak. For the composite material FeNi2S4 / Bi2O2CO3, it can be seen that the loading of FeNi2S4 effectively enhances the absorption tail peak intensity of the material, so that the light absorption of 400-800 nm is significantly enhanced, which effectively improves the visible light capture efficiency of the composite material.
[0045] Figure 3The XRD spectra of FeNi2S4 / Bi2O2CO3, FeNi2S4, and Bi2O2CO3 prepared in Example 1 and Comparative Examples 1 and 2 are shown. For FeNi2S4, the main peaks are located at 26.6°, 31.2°, 38.1°, 47.4°, 49.7°, and 54.6°, respectively, corresponding to the (220), (311), (400), (422), (333), and (440) planes of cubic FeNi2S4 (JCPDS, No. 47-1740). No impurity peaks were found, indicating that the prepared product is of high purity. For Bi2O2CO3, the XRD diffraction peaks are very consistent with the standard PDF card (JCPDS84-1752), and the diffraction peaks at 13.1°, 24.1°, 26.3°, 30.5°, 32.8°, 39.4°, 42.1°, 46.8°, 52.3° and 57.1° represent the (040), (121), (080), (161), (002), (0120), (280), (202), (2120) and (163) planes, respectively. At the same time, its main diffraction peaks are retained in the composite material FeNi2S4 / Bi2O2CO3, indicating the successful synthesis of the material. And the composite method has no obvious effect on the crystal form of the material.
[0046] Embodiment 2,
[0047] A method for preparing a novel iron-nickel-sulfur-based heterojunction catalytic material, characterized by comprising the following steps:
[0048] A. 1.04 g Ni(NO3)3·6H2O, 0.728 g Fe(NO3)3·9H2O and 7.28 g urea were dissolved in 50 mL deionized water in sequence, and then 0.728 g ammonium fluoride was added to the above solution. After magnetic stirring at 600 r / min for 30 min, the solution was centrifuged and washed 3-6 times with deionized water and ethanol, and the yellow powder was collected and dried at 60 °C for 24 h to obtain the iron-nickel material precursor; then 1.0 g of the iron-nickel material precursor was mixed with 1.2 g thioacetamide (sulfur source) and dissolved in 70 mL ethanol, the suspension was magnetically stirred at 600 r / min, and heated at 100 °C for 6 h, centrifuged, washed with ultrapure water and anhydrous ethanol for 6 times, and dried in an oven at 60 °C for 24 h to obtain black powder FeNi2S4;
[0049] B. Dissolve 1.0 g FeNi2S4, 4.912 g Bi(NO3)3·5H2O and 1.0 g urea in 90 mL deionized water. After mechanical stirring at 600 r / min for 1 h, transfer the solution to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction and heat at 180 °C for 3 h. After the reactants are cooled, filter them, wash them with deionized water and ethanol for 3-6 times, and dry them in an oven at 60 °C for 24 h to obtain the heterojunction catalytic material FeNi2S4 / Bi2O2CO3.
[0050] Embodiment 3,
[0051] A method for preparing a novel iron-nickel-sulfur-based heterojunction catalytic material, characterized by comprising the following steps:
[0052] A. 1.04 g Ni(NO3)3·6H2O, 0.936 g Fe(NO3)3·9H2O and 9.36 g urea were dissolved in 50 mL deionized water in sequence, and then 0.936 g ammonium fluoride was added to the above solution. After magnetic stirring at 600 r / min for 30 min, the solution was centrifuged and washed 3-6 times with deionized water and ethanol, and the yellow powder was collected and dried at 60 °C for 24 h to obtain the iron-nickel material precursor; then 1.0 g of the iron-nickel material precursor was mixed with 1.6 g thioacetamide (sulfur source) and dissolved in 70 mL ethanol, and the suspension was magnetically stirred at 600 r / min and heated at 120 °C for 4 h, centrifuged, washed with ultrapure water and anhydrous ethanol for 6 times, and dried in an oven at 60 °C for 24 h to obtain black powder FeNi2S4;
[0053] B. Dissolve 1.0 g FeNi2S4, 2.029 g Bi(NO3)3·5H2O and 0.75 g urea in 80 mL deionized water. After mechanical stirring at 600 r / min for 1 h, transfer the solution to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction and heat at 220 °C for 1 h. After the reactants are cooled, filter them, wash them with deionized water and ethanol for 3-6 times, and dry them in an oven at 60 °C for 24 h to obtain the heterojunction catalytic material FeNi2S4 / Bi2O2CO3.
[0054] 1. Evaluation of photocatalytic degradation performance
[0055] The photocatalytic degradation performance of FeNi2S4 / Bi2O2CO3, FeNi2S4 and Bi2O2CO3 prepared in Example 1 and Comparative Examples 1 and 2 was evaluated respectively by the following method:
[0056] The photodegradation process was carried out in a 250 mL custom-made double-walled quartz beaker with a cooling water circulation system to keep the reaction temperature constant. A 300 W xenon lamp (λ>420 nm) was used as a visible light source with an average light intensity of 200 mW / cm 2 . Before the reaction started, 50 mg of each FeNi2S4 / Bi2O2CO3, FeNi2S4, and Bi2O2CO3 were dispersed in 100 mL of bisphenol A solution (5 mg / L), and the pH value was controlled at about 7 with 0.1 M hydrochloric acid or sodium hydroxide solution. The suspension was stirred continuously during the entire reaction process. A dark adsorption experiment was performed 30 minutes before illumination to achieve the adsorption-desorption equilibrium between bisphenol A and the photocatalyst. Then, 1 mM PMS (permonosulfate) was added. During the photodegradation process, 1 mL of the reaction solution was taken out at regular intervals and then passed through a filter with a specification of 0.22 μm to prepare for ultra-high performance liquid chromatography analysis. The mobile phase was acetonitrile and ultrapure water (volume ratio of 50:50) and the detection wavelength was 278 nm. The relative concentration (C / C0) was used to calculate the degradation efficiency.
[0057] Figure 4 The performance comparison chart of FeNi2S4 / Bi2O2CO3, FeNi2S4 and Bi2O2CO3 prepared in Example 1 and Comparative Examples 1 and 2 for photocatalytic degradation of bisphenol A is shown in FIG. Figure 4 As shown, the experimental results show that: under the conditions of FeNi2S4 / Bi2O2CO3, FeNi2S4, and Bi2O2CO3 dosage of 0.5 g / L respectively, the initial concentration of bisphenol A of 5 mg / L and the initial temperature of room temperature, within 20 min, the degradation efficiency of bisphenol A by single FeNi2S4 / PMS / Vis and Bi2O2CO3 / PMS / Vis systems were 27.28% and 4.05%, respectively, while the removal rate of bisphenol A by FeNi2S4 / Bi2O2CO3 / PMS / Vis system reached 97.46%, which means that the iron-nickel-sulfur loading enables the composite material to utilize more visible light. At the same time, the construction of Z-type heterojunction effectively improves the interfacial charge transfer of photogenerated carriers and inhibits the in situ recombination of photogenerated electron-hole pairs in two single photocatalysts.
[0058] 2. Continuous degradation experiment
[0059] After the first degradation reaction of the FeNi2S4 / Bi2O2CO3 prepared in Example 1 is completed, the post-reaction solution is centrifuged and washed, and the recovered FeNi2S4 / Bi2O2CO3 is dried in a freeze dryer for 48 h, and then put into the reactor again for the next degradation experiment. Except for the materials, the other degradation reaction conditions are consistent with the setting procedures of the first photocatalytic degradation performance evaluation experiment; after the second reaction is completed, the above steps are repeated to carry out three degradation experiments.
[0060] Figure 5 This is a comparison chart of the reusability of FeNi2S4 / Bi2O2CO3 prepared in Example 1 for photocatalytic degradation of bisphenol A. Figure 5 As shown, the degradation efficiency of bisphenol A was above 90% in three consecutive degradation experiments, indicating that the photocatalytic activity of FeNi2S4 / Bi2O2CO3 photocatalytic nanomaterials remained good after three cycles. This shows that anchoring the FeNiS-based material on the bismuth subcarbonate photocatalyst is beneficial to solving the problem of material recyclability in the aqueous phase.
[0061] Organic pollutants in wastewater include but are not limited to bisphenol A, atrazine, carbamazepine, atrazine, tetracycline, rhodamine b, etc. Preferably, FeNi2S4 / Bi2O2CO3 prepared by the present invention has an exceptionally excellent degradation effect on bisphenol A under photocatalytic conditions. On the one hand, under visible light irradiation, the photocatalytic material FeNi2S4 / Bi2O2CO3 is photoexcited to generate photogenerated electrons and photogenerated holes under visible light irradiation, and the matching energy level position enables the photogenerated electrons of the FeNi2S4 conduction band to be transferred across the heterojunction interface to the Bi2O2CO3 valence band. This Z-type charge transfer mechanism not only promotes carrier separation, but also retains strong redox ability. On the other hand, the built-in electric field generated between the two under electrostatic interaction further induces electrons to migrate from FeNi2S4 to Bi2O2CO3, and the electron cross-interface transfer will effectively inhibit the recombination of electron-hole pairs, thereby significantly improving the charge separation efficiency. Finally, the pollutants are oxidized by surface active oxygen or hydroxyl groups and holes, and finally generate water and carbon dioxide.
Claims
1. A method for preparing an iron-nickel-sulfur-based heterojunction catalytic material, characterized in that The following steps are involved: A. Dissolve Ni(NO3)3·6H2O, Fe(NO3)3·9H2O and urea in deionized water in turn, then add ammonium fluoride to the solution, stir and wash, collect yellow powder, and dry to obtain an iron-nickel material precursor; then mix the iron-nickel material precursor with thioacetamide and dissolve in ethanol, stir and continue heating, centrifuge, wash, dry and collect to obtain the material FeNi2S4; B. Dissolve FeNi2S4, Bi(NO3)3·5H2O and urea in deionized water, stir and perform hydrothermal reaction, filter, wash and dry the reactants after cooling to obtain the heterojunction catalytic material FeNi2S4 / Bi2O2CO3.
2. The method for preparing an iron-nickel-sulfur-based heterojunction catalytic material according to claim 1, characterized in that: In step A, the mass ratio of Ni(NO3)3·6H2O, Fe(NO3)3·9H2O, urea and ammonium fluoride is 1:0.7-0.9:7-9:0.7-0.
9.
3. The method for preparing an iron-nickel-sulfur-based heterojunction catalytic material according to claim 1, characterized in that: In step A, the mass ratio of the iron-nickel material precursor to thioacetamide is 1:1.2-1.
6.
4. The method for preparing an iron-nickel-sulfur-based heterojunction catalytic material according to claim 1, characterized in that: In step A, the heating temperature is 100-120°C and the duration is 4-6 h.
5. The method for preparing an iron-nickel-sulfur-based heterojunction catalytic material according to claim 1, characterized in that: In step B, the mass ratio of FeNi2S4, Bi(NO3)3·5H2O and urea is 1:2-5:0.5-1.
6. The method for preparing an iron-nickel-sulfur-based heterojunction catalytic material according to claim 1, characterized in that: In step B, the temperature of the hydrothermal reaction is 180-220° C., and the time of the hydrothermal reaction is 1-3 h.
7. An iron-nickel-sulfur-based heterojunction catalytic material, characterized in that: The material is prepared by the method for preparing an iron-nickel-sulfur-based heterojunction catalytic material according to any one of claims 1 to 6.
8. Use of the iron-nickel-sulfur-based heterojunction catalytic material according to claim 7 in visible light catalytic degradation of organic pollutants.
9. The use of an iron-nickel-sulfur-based heterojunction catalytic material in visible light catalytic degradation of organic pollutants according to claim 8, characterized in that: The organic pollutants include bisphenol A.
Citation Information
Patent Citations
Visible-light responsive magnetic photocatalytic material and preparation method thereof
CN103877985A
Synthesis method and application of flower-shaped WS2 / Bi2O2CO3 heterojunction photocatalytic material
CN108786872A